Anaerobic treatment of fortified municipal wastewater in temperate climates. Issue 7 (4th December 2012) - Lester, John; Jefferson, Bruce; Eusebi, Anna‐Laura; McAdam, Ewan; Cartmell, Elise
Abstract BACKGROUND Fortification utilizes pre‐hydrolysed sludge to increase organic sewage strength for support of anaerobic development. Significantly, enhancing organic strength also permits organic loading rate to be de‐coupled from hydraulic retention time, enabling greater contact times for temperate, municipal wastewater. This study therefore describes the application of fortification to facilitate anaerobic treatment of crude wastewater in temperate climates. RESULTS Fortification with primary sludge significantly increased methane (CH4) from 0.021 m3CH4 m‐3 for crude wastewater to 0.095 m3CH4 m‐3. This increased yield demonstrates that fortification enables methane yields equivalent to conventional full‐flow anaerobic treatment through only partial treatment of wastewater (up to 50%) which lowers both capital and operational costs. Total chemical oxygen demand (COD) and soluble COD removals of 89% and 5 % were recorded following fortified crude wastewater treatment, permitting a similar effluent COD profile to treated crude wastewater. Pre‐hydrolysis of the fortified wastewater maximized methane production to 0.156 m3CH4 m‐3. Furthermore, a similar yield was reported for wastewater fortified with pre‐hydrolysed waste activated sludge, providing new opportunities for on‐site treatment with concomitant benefits in sludge reduction and enhanced energy production. Solids breakthrough occurred with pre‐hydrolysed fortification and reduced effluent quality; it is postulated that optimizing pre‐treatment and upflow velocity will improve effluent quality to that attained with standard fortification. However, fortification also reduced losses of dissolved methane in the effluent stream. CONCLUSIONS With a reduction in aeration requirements and potential savings in primary treatment and sludge treatment, fortification represents a major advance upon current practice. © 2012 Society of Chemical Industry